(3GdadGMI GdfHWjIs - (3GHf hMTjI , CMeO Hf Ydj Hf bjS Hf GdeNJGQ Hf YHO GdcQje Hf MQKjG, CHh HcQ,J (B291 (3g` s
(3BNQgG (B:s
(3GPG cGf jMJhi Ydi EUdGM ehGJ GdCQV hJOHjQGJgG hYdGLGJgG ef COhGFgG hUQa GdegGdc Yf GdTLQ hGdfNd hGdcQe s
(3eJQLe Yf GdcdOGfjIs
(3eUhQI Yf eNWhWI ecJHI GdSjO YHO GdMi GdcJGfi HGdeZQHs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
Keywords: (3GdRQGYI h GdCYTGHs